2017
DOI: 10.1038/ncomms15038
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted neuronal maturation in Angelman syndrome-derived induced pluripotent stem cells

Abstract: Angelman syndrome (AS) is a neurogenetic disorder caused by deletion of the maternally inherited UBE3A allele and is characterized by developmental delay, intellectual disability, ataxia, seizures and a happy affect. Here, we explored the underlying pathophysiology using induced pluripotent stem cell-derived neurons from AS patients and unaffected controls. AS-derived neurons showed impaired maturation of resting membrane potential and action potential firing, decreased synaptic activity and reduced synaptic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
107
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(112 citation statements)
references
References 65 publications
3
107
0
2
Order By: Relevance
“…Another CRISPR approach to understand genotype‐phenotype relationships is to introduce specific mutations. For example, an edited cell line with disrupted Angelman syndrome UBE3A gene showed impaired neuronal maturation and replicated the cellular phenotype observed in stem cell‐derived neurones from patients with Angelman syndrome …”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Another CRISPR approach to understand genotype‐phenotype relationships is to introduce specific mutations. For example, an edited cell line with disrupted Angelman syndrome UBE3A gene showed impaired neuronal maturation and replicated the cellular phenotype observed in stem cell‐derived neurones from patients with Angelman syndrome …”
mentioning
confidence: 59%
“…For example, an edited cell line with disrupted Angelman syndrome UBE3A gene showed impaired neuronal maturation and replicated the cellular phenotype observed in stem cell-derived neurones from patients with Angelman syndrome. 5 Beyond technical issues, a number of bioethical aspects must still be addressed. Yet, among many obstacles that remain before genome editing becomes a viable treatment for neurodevelopmental disorders, the main one may be our current lack of understanding of human neural function.…”
mentioning
confidence: 99%
“…Whole cell patch-clamp electrophysiology was performed on neurons differentiated from rs2832407 A/A and C/C iPSCs using previously described techniques (Lemtiri-Chlieh and Levine, 2010; Fink et al, 2017). Neurons were selected for recording based on morphology, including pyramidal-shaped soma and the presence of neurites.…”
Section: Electrophysiologymentioning
confidence: 99%
“…In the late stage of neuronal development and maturation, the resting membrane potential exhibits depolarization, decreased spontaneous excitatory postsynaptic action potentials, decreased neuron activity, and decreased synaptic plasticity. In combination with the CRISPR/Cas9 gene‐editing technique, it was demonstrated that the depolarization of the resting membrane potential induced by the UBE3A mutation might be an important cause of altered cell activity . Chen et al explored the underlying pathophysiology using iPSC‐derived neurons from patients with Angelman syndrome and unaffected controls and found that the long noncoding RNAs (lncRNAs) RNA‐binding protein fox‐1 homolog (RBFOX1) and RBFOX2 were downregulated in Angelman syndrome neurons.…”
Section: Ipsc Studies On the Molecular Mechanisms Of Gementioning
confidence: 99%
“…In combination with the CRISPR/Cas9 gene-editing technique, it was demonstrated that the depolarization of the resting membrane potential induced by the UBE3A mutation might be an important cause of altered cell activity. 89 Chen et al 90 explored the underlying pathophysiology using iPSCderived neurons from patients with Angelman syndrome and unaffected controls and found that the long noncoding RNAs (lncRNAs) RNA-binding protein fox-1 homolog (RBFOX1) and RBFOX2 were downregulated in Angelman syndrome neurons. When UBE3A was overexpressed, the differentiation abnormalities in the immature cells were rescued.…”
Section: Mutations Affecting Neurite Maturationmentioning
confidence: 99%